(untitled) (Annals of Medical Research, 2021)
Aim: Laparoscopic cholecystectomy is the optimal surgical treatment for benign gallbladder diseases. Under curtain conditions it is very hard to distinguish the Calot triangle and it becomes difficult to perform safe cholecystectomy. Subtotal cholecystectomy is a salvage option in such conditions. The aim of this study is to compare the results of open and laparoscopic subtotal cholecystectomy in difficult gallbladder management.Material and Methods: In this retrospective study results of all consecutive patients who were performed subtotal cholecystectomy between July 2014 and August 2017 were collected and laparoscopic and open methods were compared. Results:Forty-five of 396 laparoscopic cholecystectomy cases underwent subtotal cholecystectomy during the study period. Subtotal cholecystectomy was performed laparoscopically in 27 of 45 patients (Group I), and open method in 18 patients (Group II). Convertion rate was %34.1. No significant difference was observed in terms of both preoperative and postoperative laboratory results. There was no difference between two groups in terms of ERCP history. The rate of open operation was statistically higher in acute cases. The duration of surgery was significantly higher in laparoscopic group but length of hospital stay was significantly higher in open group. Total cost was higher in group 2 but this result did not reach statistical significance. Total bile leak rate was 2.2%.Conclusion: Laparoscopic subtotal cholecystectomy is a safe and appropriate method which can be compared with open subtotal cholecystectomy in difficult gallbladder management.